PRODUÇÃO AUDIOVISUAL, EDUCAÇÃO EM SAÚDE E CINECLUBISMO - Flores, Andressa M.; Martins, Lairton B.; Junior, João J. d. B.; Flores, Júlia S.; Andreola, Karine; Pich, Roselene; Martins, Ricardo V.; Gonçalves, Katiussa; Bandeira, Danieli; Maron, Luana C.; et al. (Salão do Conhecimento, 2013)
Resumo